Childhood aplastic anaemia with paroxysmal nocturnal haemoglobinuria clones: A retrospective single-centre study in South Africa - Candice L. Hendricks; Ashen Naidoo; Rajendra Thejpal; Nadine Rapiti; Beverley Neethling; Yasmin Goga; Suvarna Buldeo (AOSIS, 2022)
Background: Paroxysmal nocturnal haemoglobinuria (PNH) clones in children are rare but commonly associated with aplastic anaemia (AA) and myelodysplasia. Objective: This study aimed to determine the prevalence of PNH clones in paediatric patients with idiopathic AA, identify differences in clinical and laboratory features and outcomes, and determine the impact of clone size on clinical presentation. Methods: Patients with confirmed idiopathic AA who were tested for PNH between September 2013 and January 2018 at the Inkosi Albert Luthuli Central Hospital, Durban, KwaZulu-Natal, South Africa, were included. PNH clones were detected in neutrophils and monocytes by flow cytometry using fluorescent aerolysin, CD24, CD66b and CD14. Results: Twenty-nine children with AA were identified and 11 were excluded. Ten patients (10/18, 55.6%) had PNH clones ranging from 0.11% to 24%. Compared to the PNH-negative group, these children were older (median: 10 years vs 4 years, p = 0.02) and had significantly lower total white cell counts (median 1.7 × 109/L vs 3.2 × 109/L; p = 0.04). There was no difference in median absolute neutrophil count or haemoglobin concentration. Four patients in each group received immunosuppressive therapy (IST). At six months, all four patients with PNH clones had responded, compared to one in the PNH-negative group. Conclusion: More than half of children with AA had a PNH clone. The size of the clone did not impact clinical severity; however, IST use may positively impact prognosis. We recommend early initiation of IST in patients with AA to avoid delays associated with human leukocyte antigen typing.